Strongmen and Religious Leaders in Java: Their Dynamic Relationship in Search of Power - Pribadi, Yanwar (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2011)
The central purpose of this paper is to explore the dynamic relationship between Javanese strongmen and religious leaders in search of power. Two groups of strongmen –jago in Central and East Java and jawara in Banten– and religious leaders, such as kyai, tarekat teachers and guru ngaji are the subjects of this discussion. I present two groups of strongmen and religious leaders and sketch how both groups, through their socio-political as well as religious roles, preserve the values of the Javanese and Bantenese. Religious leaders and strongmen have been the source of informal traditional leadership, particularly in villages. Religious leaders have represented leadership in knowledge, while strongmen have represented leadership with regard to braveness and physical magical power. The most visible roles of the strongmen are as power brokers. In the meantime, religious leaders have to be aware of the risk of being alienated and isolated from their horizontal networks within religious circles, but also more importantly, that their high position in society will gradually fade away if they place themselves too close to strongmen and the authorities.